Copper Excess Detoxification Is Mediated by a Coordinated and Complementary Induction of Glutathione, Phytochelatins and Metallothioneins in the Green Seaweed Ulva Compressa - Moenne-Munoz, A; Contreras-Arredondo, R; Gonzalez-Figueroa, A; Navarrete-Rosales, A; Gomez-Luna, M (Elsevier Masson SAS, 2019)
In order to analyze the involvement of intracellular thiol-chelators in the accumulation and detoxification of copper, the marine alga Ulva compressa was cultivated with increasing concentrations of copper such as 2.5, 5, 7.5 and 10 μM for up to 12 d, and the amount of intracellular copper, glutathione (GSH), phytochelatins (PCs) and transcripts encoding three metallothioneins (MTs) were determined. Over this exposure period and concentration range there was a linear correlation between intracellular copper and the copper concentration in the culture medium. Increases in GSH concentrations occurred mainly between days 1 and 3 and at lower concentrations of copper (2.5 and 5 μM). The level of PCs, and particularly PC2, increased from day 1 of exposure mainly at higher concentrations of copper (7.5 and 10 μM). The levels of transcripts encoding MT7 increased at day 3, whereas those of MT3 and MT6 increased between days 9–12, mainly at higher concentrations of copper. Thus in U. compressa, the initial responses to increasing intracellular copper concentrations are increases in GSH and PCs that are followed by higher levels of MTs expression, suggesting that thiol-containing peptides and proteins may participate in copper accumulation and detoxification responding in a coordinated and complementary manner. In addition, the alga was cultivated with 10 μM copper for 5 d and transferred to synthetic seawater with no copper and cultivated for 3 d. The release of copper from cells to culture medium was observed and accompanied by a similar nanomolar amount of GSH; no PCs or small proteins were detected. These results could suggest that a component of the detoxification mechanism also involves the release of copper and GSH to the extracellular medium. © 2018 Elsevier Masson SAS